2018
DOI: 10.1371/journal.pone.0207022
|View full text |Cite
|
Sign up to set email alerts
|

The impact of vitamin D supplementation on musculoskeletal health outcomes in children, adolescents, and young adults living with HIV: A systematic review

Abstract: ObjectiveHIV-positive children, adolescents, and young adults are at increased risk poor musculoskeletal outcomes. Increased incidence of vitamin D deficiency in youth living with HIV may further adversely affect musculoskeletal health. We investigated the impact of vitamin D supplementation on a range of musculoskeletal outcomes among individuals aged 0–25 years living with HIV.MethodsA systematic review was conducted using databases: PubMed/Medline, CINAHL, Web of Knowledge, and EMBASE. Interventional random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“… 39 During childhood, bone formation usually predominates over bone resorption, but the proinflammatory milieu leads to an imbalance in osteoblastic and osteoclastic activity, promoting increased bone resorption relative to formation. Other factors that can compromise skeletal development include inadequate dietary calcium, vitamin D deficiency, 25 and low levels of physical activity. 24 Although in this study, children with HIV reported lower physical activity than uninfected children, low intake of both calcium and vitamin D were common regardless of HIV status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 39 During childhood, bone formation usually predominates over bone resorption, but the proinflammatory milieu leads to an imbalance in osteoblastic and osteoclastic activity, promoting increased bone resorption relative to formation. Other factors that can compromise skeletal development include inadequate dietary calcium, vitamin D deficiency, 25 and low levels of physical activity. 24 Although in this study, children with HIV reported lower physical activity than uninfected children, low intake of both calcium and vitamin D were common regardless of HIV status.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between potential risk factors and TBLH-BMC LBM and LS-BMAD Z-scores were investigated with linear regression separately for participants with and without HIV. Adjustment was made for a priori confounders (age, sex, and pubertal stage 22 ), potential risk factors (socioeconomic status, 23 physical activity, 24 calcium and vitamin D intake, 25 and, in those with HIV, CD4 cell count, viral load, tenofovir disoproxil fumarate [TDF] exposure, and age at ART initiation 26 ), variables associated in complete case analysis with TBLH-BMC LBM or LS-BMAD Z-score (at p<0·20), and variables associated with missing status.…”
Section: Methodsmentioning
confidence: 99%
“…According to our results, supplementation with vitamin D can increase serum 25OHD levels, although this change does not appear to be related to increases in HGS. Studies conducted in children with health impairments have reported the effects of vitamin D supplementation on muscle strength (38)(39)(40) and concluded that vitamin D supplementation, in combination with a training program, significantly increased muscle strength in children with severe burns. High doses of vitamin D can improve neuromuscular motor skills in HIVpositive children.…”
Section: ' Discussionmentioning
confidence: 99%
“…This systematic review was performed following the preferred reporting items for the systematic reviews and meta-analyses (PRISMA) statement [ 20 ]. We defined the study protocol before study initiation and it was submitted to the international prospective register of systematic reviews on 15 May 2022, and accepted on 23 May 2022 (PROSPERO, accessed on 14 October 2022; registration number: CRD42022332980).…”
Section: Methodsmentioning
confidence: 99%
“…This condition could be associated with a number of disorders involving bone, cartilage, and the associated tissues. Furthermore, it could lead to reduced muscle strength and poor physical performance, and studies have shown an association between low vitamin D status and musculoskeletal disorders, such as osteoarthritis, risk of falling, and osteoporosis [ 16 , 17 , 19 , 20 , 21 , 22 ]. Moreover, among the several genes that have been associated with TMDs, the vitamin D receptor (VDR) gene is regarded as one of the most important candidate genes for investigating the genetic factors that contribute to the pathophysiology of TMDs [ 23 ].…”
Section: Introductionmentioning
confidence: 99%